INTEREST AND TALENT-BASED CAREER GUIDANCE STRATEGY IN THE DIGITAL AGE - Karunia, Marpren; Daharnis; Ifdil (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Challenges in education are increasingly complex, especially in the field of career guidance. This research aims to explore interest and talent-based career guidance strategies in the digital era. The research method used is a literature study, by analyzing various relevant research and literature related to career guidance. The results showed that effective career guidance strategies in the digital era include the integration of digital technology, the use of interactive media, comprehensive services, and multi-party engagement. Digital technologies, such as artificial intelligence-based applications and online platforms, can be used to help students understand their interests, talents and potentials in a more personalized manner. In addition, a comprehensive approach through basic, responsive, individualized planning and system support services provides holistic guidance for students in making career decisions. This strategy is also reinforced by life skills training and collaboration with parents, teachers, psychologists and industry professionals. This study concludes that interest and talent-based career guidance that utilizes digital technology can increase the effectiveness of career counseling services, have a positive impact on students' readiness to face the challenges of the world of work, and support career development in accordance with individual potential. This study provides recommendations for counselors and educational institutions to continue to innovate in providing career guidance services that are relevant to the needs of the digital era.